Análise de juntas soldadas de aço API 5L X-70 com laser Nd: YAG pulsado - Sanitá, Willian Roberto Valicelli [UNESP] (2017)
We carried out a study of laser welding provided "bead on plate" in micro-alloyed steel ARBL API 5L Gr. X70 in the form of plates with 1,0 x 20 x 120 mm (H x W x D). 12 welds was performed in argonic gas flow of 15 l/min, beam diameter 0,2 mm, angle of 90°, repetition rate of 9, 8, 7, 6 and 5 Hz, welding speed of 1 mm/s, gas depths focus equal to 0,57 mm below the surface of the workpiece and the pulse energy (Ep) set at 10,0 J. The time width (Lt) set at 10 ms. The heat input was varied at 90, 80, 70, 60 and 50 J/mm. The results were analyzed based on the relationship between power, weld bead geometry, corrosion, Vickers hardness, chemical analysis and microstructure. For structure revelation of the weld metals used both Nital 5%. Measures of geometry (width and depth) of the weld beads were made using images taken by digital camera on an ordinary optical microscope. Microscopy tests were carried out using a scanning electron microscope in a backscattered detector (BSD), in order to verify with greater clarity the microstructures of the samples. For verification of mechanical strength was tensile test on samples and base metal without notch insertion. For verification of hardness were analyzed four parameters being three horizontal lines and a vertical line in the center of the weld bead. To verify the corrosion, a potentiostat test was conducted for potentiodynamic polarization test where the polarization curves were analyzed. The greatest values of depth width were found in higher values of power and temporal width. The microstructures of the samples showed formations of acicular ferrite, allotriomorphic ferrite and possible high martensite contents in the case of samples with lower heat input (60 and 50 J / mm). All samples showed higher mechanical strength than the base metal, since all of them broke in the base metal. The coefficients of hardness were higher for samples with lower thermal input. The corrosion resistance remained close to the base metal and some higher cases (Ap 70 J / mm), since a passive oxide film probably formed after welding, resulting in higher strength.